Zinc concentrations in different parts of the gastropod, faunus ater, collected from intertidal areas of Peninsular Malaysia - Kong Yap, Chee; Kumar, Krishnan; MND, Hisyam; Cheng, Wan Hee; Syazwan, Wan Mohd; Azrizal-Wahid, Noor; Nulit, Rosimah; Ibrahim, Mohd. Hafiz; Mustafa, Muskhazli; Okamura, Hideo; Horie, Yoshifumi; Sharifinia, Moslem; et al. (SciRes Literature LLC, 2022)
Intertidal gastropods, Faunus ater (F. ater), were collected from four sampling sites in Peninsular Malaysia. It was found that the concentrations of Zinc (Zn) (mg/kg dry weight) ranged from 347.23 to 356.21 for Digestive Caecum (DC), 95.00 to 100.91 for foot, 102.73 to 109.00 for muscle, 42.73 to 177.72 for operculum, 87.57 to 161.76 for remainder, and 24.42 to 53.96 for shell of F. ater. Current results indicate that the intertidal waters of Pantai Sri Tujoh has a higher bioavailability of Zn and require further research. According to the current findings, F. ater may be employed as a biomonitor of Zn pollution and bioavailability.